Career breaks, broken pensions? Long-run effects of early and late-career unemployment spells on pension entitlements - Bravo, Jorge M. (2022)
Bravo, J. M., & Herce, J. A. (2022). Career breaks, broken pensions? Long-run effects of early and late-career unemployment spells on pension entitlements. Journal of Pension Economics and Finance, 21(2), 191 - 217. [Advanced online publication on 22 July 2020]. Doi: https://doi.org/10.1017/S1474747220000189